Tingkat Pemahaman 7 Prinsip HACCP pada Pelaku UMK Makanan dan Minuman Kecamatan Kenjeran Kota Surabaya - Saputro, Andre Ridho; Adiaksa, Fitrah Thoriq; Putra, Andhika Cahyono (Universitas Muhammadiyah Surabaya Publishing, 2023)
Kenjeran is one of the sub-districts in the city of Surabaya. The majority of local residents' livelihoods are as food and beverage SME. To maintain food quality and safety, an analysis is needed to identify the dangers that exist during the process of making food or beverage products and provide recommendations for developing a food safety system, namely through the HACCP (Hazard Analysis and Critical Control Point) system. There are 7 main principles that exist in the HACCP system which consists of 24 questions distributed to MSME actors in Kenjeran District, Surabaya City. Validation and reliability tests were carried out on each question item using the Cronbach's alpha method. Based on the results of descriptive statistical analysis using the mean (average) and mode methods, it can be concluded that the value produced in the analysis dominates number 3 and the highest average value is found in principle 6 with an average of 3.16. From this average value, it can be interpreted that the level of understanding of MSME actors in Kenjeran District, Surabaya City is quite understanding or often enough in checking and cleaning raw materials, production processes and workers in the production environment. There are several principles that have a low average value, namely principle 1 of 2.87 and principle 5 of 2.89, meaning that it can be said that the level of understanding of SME actors in Kenjeran District, Surabaya City is somewhat lacking. Improvements that can be made are by conducting training and counseling regarding the HACCP system which must be followed by all SME actors, whether from Kenjeran District or other sub-districts in the city of Surabaya, as well as increasing government regulations regarding increasing resources to prepare SME actors who are better prepared.